Big Data, Sentiment Analysis, and Examples during the COVID-19 Pandemic - Diareme, Kyvele Constantina; Liapakis, Anastasios; Efthymiou, Iris (HAPSc Policy Briefs Series, 2022)
Applied research in Big Data has gained popularity and is already transforming corporations, public sector, health care and subsequently everyday life. Big Data are being analysed for a variety of reasons, e.g., predict Brexit negotiating outcomes, optimise operations in agriculture, map and analyse human mobility trends under non-pharmaceutical interventions during the recent pandemic. The period of the COVID-19 pandemic has been characterised also by an ‘infodemic’, meaning an overabundance of both good and bad information. This information needs to be managed effectively as it can yield valuable insights when analysed. In this paper the terms of Big Data, Geospatial Big Data and Sentiment Analysis are presented along with selected cases, from the international literature, of the use of Big Data and analytics during the COVID-19 pandemic.